2012
DOI: 10.1100/2012/565413
|View full text |Cite
|
Sign up to set email alerts
|

An Investigation of Current Endodontic Practice in Turkey

Abstract: Objectives. The aim of this study was to gather information about the quality and quantity of root canal treatments carried out by general dental practitioners in Turkey. Methods. Questionnaires were given to 1400 dentists who attended the 16th National Congress organized by the Turkish Dental Association. The participants were asked to answer 34 multiple-choice questions. The questions were subdivided into 3 main topics; general information; general approach to endodontic treatment; and cleaning, shaping, and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
26
0
14

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(46 citation statements)
references
References 19 publications
6
26
0
14
Order By: Relevance
“…2 For accurate determination of working length a combination of electronic apex locator (EAL) and radiographs is important but about 39.9% of the respondents relied exclusively on radiographs in our study while 16.1% relied on a combination of radiographs and apex locator. 18 These findings are similar to those reported by Kaptan et al 5 and others 6,7,9,14,15 but differs from those reported by Savani et al, 1 Kohli et al2 and Raoof et al8. Lee et al showed even in USA about half of the endodontists relied on EAL for length determination, considering which the results from Pakistani population are encouraging in terms of adoption of new technology.…”
Section: Discussionsupporting
confidence: 82%
See 3 more Smart Citations
“…2 For accurate determination of working length a combination of electronic apex locator (EAL) and radiographs is important but about 39.9% of the respondents relied exclusively on radiographs in our study while 16.1% relied on a combination of radiographs and apex locator. 18 These findings are similar to those reported by Kaptan et al 5 and others 6,7,9,14,15 but differs from those reported by Savani et al, 1 Kohli et al2 and Raoof et al8. Lee et al showed even in USA about half of the endodontists relied on EAL for length determination, considering which the results from Pakistani population are encouraging in terms of adoption of new technology.…”
Section: Discussionsupporting
confidence: 82%
“…A sample from academic institutes was selected because it was believed that an academic environment encourages practitioners to adopt more evidence based practice. The 79% response rate is encouraging for this study as other such surveys performed in different countries had a much smaller response rate, 24% for Savani et al, 35% for Lee et al, 42% for Kohli et al, 43% for Kaptan et al 1,2,5,7 However, surveys performed by Raoof et al in Iran and Gupta et al in India have demonstrated a relatively higher response rate of 84.88% and 88% respectively. 8,9 Establishing a proper diagnosis is the first step in delivering appropriate treatment to a patient, various aids have been recommended to help guide the endodontist in this task.…”
Section: Discussionsupporting
confidence: 50%
See 2 more Smart Citations
“…A study conducted in Denmark noted that only 10% of general dental practitioners used rotary nickel-titanium instruments [21]. A further observation could be made that the younger generation used step back technique more often that the older, where the aforementioned technique uses mainly only K-files [8]. Comparable results were acquired in the present study whereas the professionals age, the step back technique fades out in usage and the usage of rotary system becomes more prominent.…”
Section: Discussionsupporting
confidence: 76%